MANAJEMEN PRODUKSI SIARAN DIGITAL PROGRAM PENYEJUK QALBU DI LEMBAGA PENYIARAN PUBLIK TELEVISI REPUBLIK INDONESIA (TVRI) RIAU - Ardiansyah, Arga; Rimayanti, Nita (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Digital broadcasting is a technological development, Digital broadcasting is a new format that has many advantages of qualities such as; image, audio, and network. The one of program in Televisi Republik Indonesia (TVRI) that use digital broadcasting is Penyejuk Qalbu’s program. This program discuss about the islamic religion, this program also use the musical instrument that is Rebana. The purpose of this research is to knowing how to the production management of digital broadcasting from Penyejuk Kalbu program in the TVRI Riau.This research use qualitative methods with descriptive approach. The object of this research is the production management of digital broadcasting from Penyejuk Kalbu program in the public broadcaster of Telivisi Republik Indonesia (TVRI) Riau produced by TVRI Riau. The subject of this research is six persons as informant that is the head division of program section TVRI Riau, the producer of penyejuk qalbu program, presenter program, and transmitter technician. The technique of data collection in this research is interview, observation, and documentation.The result of this research is explained how to implement the methods of planning, organizing, actuating, and controlling (POAC)in production management of digital broadcasting from Penyejuk Kalbu program to produce the quality broadcasts.The digital broadcasting from Penyejuk Kalbu programaplly 4 steps to make the quality broadcasts; the first is Planning, to determine the program and broadcast background, Content Planning, placement team for work in the individual worker, The second step is organizing, the digital broadcaster has been determined the worker in accordance with the capability, the third step is movement, begins with coverage in the studio, the placement of worker position, recording, sound proofing, and then broadcasting program in the transmitter room, the fourth step is controling and evaluation. The evaluation for make sure everysteps from program coverage to program broadcasting that is goes well, so this digital broadcasting can be enjoyed by riau people.Keywords: Management, Digital broadcast, Television Programs